2016
DOI: 10.1016/j.lwt.2015.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the kinetics of Listeria monocytogenes in refrigerated fresh beef under different packaging atmospheres

Abstract: a b s t r a c tThe objective of this study was to model the fate of Listeria monocytogenes inoculated in beef at two concentrations (2.5 and 4.0 log CFU/g), packaged under air, vacuum and three modified atmospheres MAP: 70%O 2 /20%CO 2 /10%N 2 , 50%O 2 /40%CO 2 /10%N 2 and 30%O 2 /60%CO 2 /10%N 2 , and refrigerated at a normal temperature (4 C) and at a mild abusive temperature (9 C). The experimental design produced a total of 20 environmental conditions. An omnibus model based on the Weibull equation proved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 25 publications
5
20
0
Order By: Relevance
“…monocytogenes growth in vacuum-packaged beef stored at 0 and 5 C. They indicated that growth of this bacteria on beef depends on the storage temperature, pH and the type of tissue (fat or lean). Although L. monocytogenes grows at both temperatures, a scarce lag period was observed in beef stored at 5 C. Similarly, [35] observed an increase of lag phase of L. monocytogenes in beef samples stored at 4 C compared to those stored at 9 C. In a study with pork cuts [38] stored at mean refrigerator temperatures did not increase the populations of L. monocytogenes over 2 log CFU/g in the end of product shelf-life. However, at abusive temperatures, microbial counts were higher than 3 log CFU/g for some cases, which required a more severe heat inactivation treatment before consumption.…”
Section: Packagingmentioning
confidence: 80%
See 3 more Smart Citations
“…monocytogenes growth in vacuum-packaged beef stored at 0 and 5 C. They indicated that growth of this bacteria on beef depends on the storage temperature, pH and the type of tissue (fat or lean). Although L. monocytogenes grows at both temperatures, a scarce lag period was observed in beef stored at 5 C. Similarly, [35] observed an increase of lag phase of L. monocytogenes in beef samples stored at 4 C compared to those stored at 9 C. In a study with pork cuts [38] stored at mean refrigerator temperatures did not increase the populations of L. monocytogenes over 2 log CFU/g in the end of product shelf-life. However, at abusive temperatures, microbial counts were higher than 3 log CFU/g for some cases, which required a more severe heat inactivation treatment before consumption.…”
Section: Packagingmentioning
confidence: 80%
“…Although regarding vacuum packaging, this preservation methodology seems not affecting the growth of L. monocytogenes as observed by [16]. With reference to [35], it was showed that L. monocytogenes survives better in vacuum packaging than in air-packed beef samples. According to [36], neither L. monocytogenes grow after 42 days of storage nor significant reductions were observed in inoculated vacuum-packed beef stored at 4 C[37]obse rv edL.…”
Section: Packagingmentioning
confidence: 83%
See 2 more Smart Citations
“…The composition of modified atmosphere systems can be an effective way to reduce the growth rate of spoilage aerobic organisms and modify the microbial ecology of the product. But their effectiveness strongly depends on the initial microbial contamination of raw materials, storage temperature, film permeability and the carbon dioxide concentration used (20-40% is commonly used to suppress microbial growth) (Simpson and Carevic, 2004;Rotabakk et al, 2006;Stoops et al, 2015;Guillard et al, 2016;Saraiva et al, 2016;Couvert et al, 2017). The carbon dioxide concentration was here theoretically sufficient to limit the microbial growth.…”
Section: Discussionmentioning
confidence: 98%